SAT0051 Transcription Factor SOX5 Promotes Rheumatoid Arthritis Synovial Fibroblast Migration and Invasion by Regulating MMP9 Expression via Downregulated MIR-15A/MIR-16. (15th July 2016) - Tan, W.; Shi, Y.; Feng, X.; Wang, F.; Xuan, W.; Zhang, M.
Abstract : Background: SOX5 is known as a transcription factor which primarily involved in the regulation of embryonic development, cell fate, and chondrogenesis. To date, little is known the effect of SOX5 on rheumatoid arthritis (RA). We previously reported association between younger age at onset of rheumatoid arthritis (RA) and a RANKL promoter SNP that conferred an elevated promoter activity after stimulation via binding to a transcription factor SOX5 (Arthritis Rheum 2010; 62(10):2864–75.). Subsequently, we confirmed that SOX5 could up-regulate RANKL expression in RA synovial fibroblast (SF) and participate in the bone erosion of RA. Objectives: Here, we examine the effect of SOX5 on the migration and invasive characteristics of RA synovial fibroblasts. Methods: Rheumatoid synovial fibroblasts cell line MH7A were treated with SOX5 small interfering RNA (SOX5-siRNA) and recombinant Adenovirus SOX5 expression vectors (Ad-SOX5). Migration and invasion and of RASF was assessed by transwell matrigel™ invasion chambers and collagen gel assays. Modulation of MMP9 expression in RASF was analyzed by real-time PCR, western blot, luciferase assay and Chromatin immunoprecipitation (ChIP). Collagen-induced arthritis (CIA) DBA/1 mouse locally injected with lentivirus-shSOX5 was used to examine the effect of SOX5 on MMP9 expression in vivo. Results: Overexpression of SOX5 significantly induced cell migration, invasion and MMP-9 expression in RASF. Migration and invasion of RASF could be markedly decreased by silencing SOX5 expression but could be reverted by added the recombinant MMP9 cytokine into RASF. Overexpression of SOX5 enhanced the promoter activity of MMP9 in Hela cell. Chromatin immunoprecipitation (ChIP) showed approximately 3-fold enrichment of MMP9-specific DNA in anti-SOX5 immunoprecipitate in IL-6 treated MH7A, as compared to untreated cells. Silencing SOX5 resulted in significantly increased miR-15a/miR-16 expression in MH7A. The enhanced MMP-9 expression induced by Ad-SOX5 transfection could be inhibited by miR-15a/miR-16 mimics. Local silencing SOX5 in CIA mice inhibited the synovitis and bone erosion in CIA mice and accompanied by the markedly reduced MMP9 expression in synovium. Conclusions: These findings indicated transcription factor SOX5 plays an important role in regulating the migration and invasion and production in RA SF by modulation MMP9 expression via downregulated miR-15a/miR-16, suggesting SOX5 as a potential therapeutic target for the treatment of RA. Disclosure of Interest: None declared